Some salient features of the Bay of Bengal Cyclone of November 1989 (MAUSAM, 1991)
The cyclone which occurred in the Bay of Bengal during November 1989 produced relatively less rainfall and the damage though intensive was confined to a relatively small area. After landfall the system weakened rapidly. Salient features of the cyclone are discus3ed and a comparative study has also been made with the cyclone of November 1984 and the results presented.